From Doxastic to Epistemic: A Typology and Critique of Qualitative Interview Styles. (March 2020) - Berner-Rodoreda, Astrid; Bärnighausen, Till; Kennedy, Caitlin; Brinkmann, Svend; Sarker, Malabika; Wikler, Daniel; Eyal, Nir; McMahon, Shannon A.
Qualitative interview styles have been guided by precedent within academic disciplines. The nature of information sought, and the role of interviewer and interviewee are key determinants across styles, which range from doxastic (focused on understanding interviewees' experiences or behaviors) to epistemic (focused on co-constructing knowledge). In this article, we position common interview styles along a doxastic–epistemic continuum, and according to the role of the interviewee (from respondent to equal partner). Through our typology and critique of interview styles, we enhance epistemic interviewing by introducing "deliberative interviews, " which are more debate oriented and closer to equality in the interviewee and interviewer relationship than existing interview styles. Deliberative interviews require a comprehensive, pre-interview briefing on the subject matter followed by interactive deliberation wherein complex issues are debated across viewpoints in an effort to devise solutions. The effectiveness of this interview style in generating new knowledge warrants empirical testing across academic disciplines.